Minimizing Cost Travel in Multimodal Transport Using Advanced Relation Transitive Closure. (23rd August 2018) - Oucheikh, Rachid; Berrada, Ismail; Omari, Lahcen
Abstract : The optimization computation is an essential transversal branch of operations research which is primordial in many technical fields: transport, finance, networks, energy, learning, etc. In fact, it aims to minimize the resource consumption and maximize the generated profits. This work provides a new method for cost optimization which can be applied either on path optimization for graphs or on binary constraint reduction for Constraint Satisfaction Problem (CSP). It is about the computing of the "transitive closure of a given binary relation with respect to a property." Thus, this paper introduces the mathematical background for the transitive closure of binary relations. Then, it gives the algorithms for computing the closure of a binary relation according to another one. The elaborated algorithms are shown to be polynomial. Since this technique is of great interest, we show its applications in some important industrial fields.